Espaço público e tempo na arte visual contemporânea: os fenômenos estéticos como ação política - OLIVEIRA, Ana Jacira Borges (2017)
The expressions of the contemporary art provoke, today, a large discussion about topics not considered in the tradition of the art as institution. In this context, the ability to establish relationships between people presents itself as an opening that involves the artistic and political universe. Highlighting the space-time elements that constitute this relationship, the objective was to analyze how they are based on the aesthetic phenomenon of contemporary visual art, a potential public own of political action. This analysis is based on the political conceptions of Hannah Arendt, which involves the conditioning activities of human life on Earth, the objective nature of art, the activities of the spirit, and the author's appropriation of the Kantian judgment of taste. The context analyzed assumes importance when establishing a link between aesthetics and politics, because the taste refers to an extended thought about what appears. The analysis of the political potential of taste refers to the context in which the public space falls apart and in which an aesthetized society emerges. Considering the performance of artists who broke with the notion of beautiful and artistic object, we find in the poetic proposals of Banksy, collective woodcut Map and Beth Moysés, elements that makes up the manifestations that express the search for a relationship with the public based on the re-signification Of space and time, and that is given by the reflection about the way the places are constituted in the urban space. The notion of place was thought here, from the conceptions of the geographer Yi-Fu Tuan. Besides, the search searched sought the theoretical contribution of Anne Cauquelin, Vera Pallamin and Nicolas Bourriaud, authors who think about the proposals of contemporary art. Also, the philosopher Gilles Deleuze's reflections about the time, which dialogue with the tradition of thought concerning to the theme - especially Henri Bergson - contextualize the role it exercises in the relations occasioned by art between man and space, and which point to the Possibility of a re-signification of values from the perception of spaces and times lived. The phenomena of contemporary visual art inhabit in time and re-signify the urban space, constituting possible places of speech of the individual, as well as of the collective.